Improved toughness and delamination resistance in continuous fiber reinforced geopolymer composites via incorporation of nano-fillers. (April 2020) - Rahman, Akm Samsur; Jackson, Patrick; Radford, Donald W.
Abstract: Geopolymer matrix composites (GMC) have the potential to bridge the processing performance gap between polymer matrix and ceramic matrix composites. Yet one drawback of GMCs is their extreme brittleness and weak inter-laminar shear strength. The aim of this study was to evaluate the effectiveness of Silicon Carbide Whisker (SCW) nano-filler on the mechanical performance of neat unreinforced geopolymer and unidirectional fiber reinforced GMCs containing variations in fiber surface chemistry. In order to evaluate, neat and SCW populated geopolymer matrices were fabricated for comparison. Nextel 610 fiber reinforced GMCs were also fabricated with SCW for comparison to GMCs without the SCW nano-filler. The effect of the nano-filler was evaluated using three-point flexural methods to obtain strength and fracture toughness (KIC ). Results indicate that the addition of SCWs up to 4 vol% improved Mode-I fracture toughness of the baseline geopolymer matrix by 113%. The improvements to the neat matrix also resulted in improved flexural strength, inter-laminar shear strength, and delamination resistance of the continuous fiber reinforced composites.